Comparative analysis of the parapatellar and subpatellar approaches in reducing peripheral knee pain post-intramedullary tibial fracture surgery - Shaoyu Han; Bingjun Cui; Lang Wu; Chuangong Wang; Zhixiang Chen (BMC Surgery)
Abstract Introduction Intramedullary tibial nailing is a standard treatment for tibial shaft fractures. Postoperative knee pain significantly impacts functional recovery; however, studies on this issue are limited. This study evaluated the effect of the parapatellar approach for intramedullary nailing on postoperative knee pain. Materials and methods A total of 29 patients with tibial shaft fractures treated with intramedullary nails from March 2019 to January 2022 were divided into two groups based on the surgical approach: the semi-extended lateral parapatellar approach and the conventional subpatellar ligament split approach. Recorded metrics included operation time, intraoperative fluoroscopy count, intraoperative bleeding volume, Visual Analog Scale (VAS) scores for knee pain at 24 h, 72 h, 1 week, and 1 month postoperatively, fracture healing time and Lysholm knee functional scores at 12 months. Results Both groups completed the operation without significant differences in operation time, intraoperative bleeding, fracture healing time, or intraoperative fluoroscopy (P > 0.05). The parapatellar group showed significantly better VAS scores for knee pain at 24 h, 72 h, and 1 week postoperatively compared to the control group (P < 0.05), with no significant difference at 1 month. After 12 months, Lysholm scores indicated no significant differences in knee support, locking, and swelling (P > 0.05); however, the parapatellar group showed significant improvements in lameness, instability, stair climbing, squatting, and pain (P < 0.05). Overall, the parapatellar group outperformed the control group (P = 0.01). Additionally, long-term follow-up revealed potential advantages of the parapatellar approach in improving long-term functional outcomes. Conclusions Using the parapatellar approach for tibial intramedullary nailing avoids splitting the patellar ligament and entering the joint cavity, minimizing knee joint impact and effectively reducing postoperative knee pain, with potential benefits in long-term functional recovery.